The Popular Classes and Royal Justice in Medieval England: Evidence from the Derbyshire Eyre of 1330-1331 - Chris Briggs (Studia Historica. Historia Medieval)
This article investigates the degree to which England’s royal courts of common law were used by the masses (peasants, craftsmen, wage-earners) to prosecute lawsuits of small value. It argues that this issue is important for understanding the institutional framework that supported England’s developing market economy, and for investigating claims about state formation in this period. Using a case study of one particular provincial session of royal justice —the Derbyshire eyre of 1330-31— the article presents quantitative evidence on the social status and subject matter of debt and trespass business heard before the king’s justices. It is argued that the Derbyshire evidence shows that there were limits to the social reach of the common law courts. If we wish to grasp the framework of civil justice we must aim at a more comprehensive analysis of medieval England’s multifarious jurisdictions (royal, communal, urban, seigniorial, and ecclesiastical).